2021
DOI: 10.3390/molecules26113316
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Characterization in a Model of Nonalcoholic Steatohepatitis with Fibrosis; A Call for Development of Targeted Therapeutics

Abstract: Left untreated, nonalcoholic fatty liver disease can progress to nonalcoholic steatohepatitis (NASH), fibrosis, and end-stage liver disease. To date, few if any therapies have proven effective against NASH with fibrosis. Quantification and qualification of hepatic scar might enable development of more effective targeted therapies. In a murine model of NASH induced by diet, we characterized fibrillar collagen deposition within the hepatic parenchyma. At harvest, livers from the modified diet cohort exhibited NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Collagen is the principal component of the extracellular matrix or scars. A recent study showed that NASH with fibrosis is associated with upregulation of hepatic fibrillar collagen genes, namely, COL I and COL III [61]. Most studies on animals fed an HFD diet for a duration of less than 4 months showed that there were no significant changes in the expression of genes encoding proteins involved in the fibrogenesis pathway; however, such changes were found to be significant in studies with a longer duration from 24-25 weeks of exposure to HFD [22,45] (Table 5).…”
Section: Fibrogenesis Pathwaymentioning
confidence: 99%
“…Collagen is the principal component of the extracellular matrix or scars. A recent study showed that NASH with fibrosis is associated with upregulation of hepatic fibrillar collagen genes, namely, COL I and COL III [61]. Most studies on animals fed an HFD diet for a duration of less than 4 months showed that there were no significant changes in the expression of genes encoding proteins involved in the fibrogenesis pathway; however, such changes were found to be significant in studies with a longer duration from 24-25 weeks of exposure to HFD [22,45] (Table 5).…”
Section: Fibrogenesis Pathwaymentioning
confidence: 99%
“…We explored lncRNA responses in chronic CCl 4 -exposed liver, a widely used model for chemical-induced liver fibrosis and identified 631 lncRNAs dysregulated in or more hepatic mesenchymal cell populations. Validating this model, we observed strong up regulation of many HSC-expressed lncRNAs in association with the up regulation of PCGs involved in extracellular matrix and collagen processes, a key feature of HSC activation and liver fibrosis 128 . Further, spatial inference analysis revealed apparent zonation differences between control and fibrotic HSCs.…”
Section: Discussionmentioning
confidence: 72%
“…The major fibrillar collagens abundantly expressed in liver fibrosis are Collagen 1 and Collagen 3 ( Pellicano et al, 2021 ). We have investigated both ICV and IP CBX groups to evaluate our previous findings further and investigate possible treatment targets by mitigating excessive fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We have checked the Collagen 1 and Collagen 3 expression in spinal cord sections and pointed accumulation of Collagen 3 in the PLP group, and prevention of perivascular fibrosis by CBX treatment. One possible explanation for this could be that extensive Collagen 1 accumulation is the hallmark of advanced fibrosis in the liver; whereas, fibrillar Collagen 3 expression starts in the early stages and gradually increases regarding the severity of the disease ( Pellicano et al, 2021 ). We showed that IP CBX did not alter the collagen 3 production but ICV CBX significantly decreased the Collagen 3 accumulation in-vivo .…”
Section: Discussionmentioning
confidence: 99%